Income Disparities in the Association of the Medical Home With Child Health. (June 2018) - Anker, Bryan; Tripodis, Yorghos; Long, Webb E.; Garg, Arvin
This study was a secondary data analysis of the 2011-2012 National Survey of Children's Health. Data were available for a nationally representative sample of 81 090 children. Multivariable logistic regression was used to model child health with the medical home while examining the effect modification of household income and controlling for sociodemographic characteristics. Overall, the medical home was significantly associated with "excellent/very good" child health for children regardless of household income. However, the association of the medical home with "excellent/very good" child health was significantly higher for children in households earning >200% FPL (federal poverty level) compared with <200% FPL (adjusted odds ratio [aOR] 2.13 [95% CI 1.80-2.52] vs aOR 1.46 [95% CI 1.24-1.71]; P < .01). This relationship was also found among children >400% FPL compared with children between 100% and 199% FPL (aOR 2.25 [95% CI 1.74-2.9 0] vs aOR 1.28 [95% CI 1.01-1.62]; P < .01). Therefore, while the medical home is associated with beneficial child health for most children, significant disparities by income exist.